Health care: heart rate measurement / Mohamad Jazli Jamaludin, Farah Wahida Risdianto and Hanis Nadzirah Hishamuddin - Jamaludin, Mohamad Jazli; Risdianto, Farah Wahida; Hishamuddin, Hanis Nadzirah (2014)
This project describes the design of a simple, low-cost microcontroller based heart rate measuring device. The result display at LCD .Measure heart rate is important to health care. Hearth is important body part to human.Heart rate measurement machine in this project for measure from finger using IR sensor.lR sensor act as transmitter and photodiode receive signal from transmitter. So,the photo diode is a receiver. Heart rate exhibiting direct proportional characteristics with change in blood volume during heart beats can be measured by modelling an analog and digital manipulation scheme. In this project used two -stage high gain, active low pass filter using two Operational Amplifier(Op-amp) ) to filter and amplify the signal to appropriate voltage level so that the pulses can be counted by a microcontroller.. This project use PIC16877A as microcontroller to connect to led and two stage filter. In project, we set the time to count is 15 second and the result multiplied with 4 for get one minute heart beat.